2022
DOI: 10.3390/biomedicines10092180
|View full text |Cite
|
Sign up to set email alerts
|

Myosins and MyomiR Network in Patients with Obstructive Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common genetic cardiomyopathy. The molecular mechanisms determining HCM phenotypes are incompletely understood. Myocardial biopsies were obtained from a group of patients with obstructive HCM (n = 23) selected for surgical myectomy and from 9 unused donor hearts (controls). A subset of tissue-abundant myectomy samples from HCM (n = 10) and controls (n = 6) was submitted to laser-capture microdissection to isolate cardiomyocytes. We investigated the relationship amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…miRNAs act mainly by regulating gene expression at the post-transcriptional level, either by directing their target mRNAs to be degraded or by inhibiting their translation. Several studies have shown that miRNAs are key players in heart remodeling, including hypertrophy and fibrosis, in in vivo disease models and in vitro [ 39 , 40 , 41 , 42 ]. Overexpression of miRNA-195 leads to cardiac pathological hypertrophy and heart failure in mice [ 43 ].…”
Section: Mirnas In Remodeling In Dyssynchronous Heartsmentioning
confidence: 99%
“…miRNAs act mainly by regulating gene expression at the post-transcriptional level, either by directing their target mRNAs to be degraded or by inhibiting their translation. Several studies have shown that miRNAs are key players in heart remodeling, including hypertrophy and fibrosis, in in vivo disease models and in vitro [ 39 , 40 , 41 , 42 ]. Overexpression of miRNA-195 leads to cardiac pathological hypertrophy and heart failure in mice [ 43 ].…”
Section: Mirnas In Remodeling In Dyssynchronous Heartsmentioning
confidence: 99%
“…Genetic HCM and DCM are characterized by shorter telomeres in cardiomyocytes [142], with a correlation between hypertrophic phenotype severity and leukocyte telomere length [143]. Myosins and myosin-encoded microRNA networks may explain phenotype differences and could represent putative therapeutic targets in HCM patients [144].…”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…Finally, the sequencing of the entire human genome in 2003 brought a huge boost in understanding the genetic background of diseases. Nowadays, medical science is moving beyond the border of the genome towards new horizons (proteome, metabolome, and epigenome) in order to bridge the gap between genotype and phenotype [ 3 , 4 ]. Personalized medicine (PM) was defined by Horizon 2020 Advisory Group as “ a medical model using characterization of individuals’ phenotypes and genotypes for tailoring the right therapeutic strategy for the right person at the right time, and/or to determine the predisposition to disease and/or to deliver timely and targeted prevention ” [ 5 ].…”
Section: Introductionmentioning
confidence: 99%